THE EFFECT OF CURRENT RATIO, INVENTORY TURNOVER, DEBT TO EQUITY RATIO, AND NET PROFIT MARGIN ON THE VALUE OF COMPANIES IN THE HEALTHCARE SECTOR LISTED ON IDX 2017-2020 - Redy Herinanto Albertus; Syaiful Syaiful (UPMI Management, 2022)
This study aims to analyze the effect of current rasio, inventory turnover, debt to equity rasio, and net profit margin to the Value of Companies in the Healthcare Sector listed on the Indonesia Stock Exchange in 2017-2020. The research method used is quantitative method. The sampling technique used is purposive sampling with a total population of 23 companies. Retrieval of company secondary data through BEI, company official website Yahoo finance and IDN Financial. The data analysis used in this study is the classical assumption test, multiple linear regression analysis and hypothesis testing using the SPSS 25 application. Based on the results of the study, it shows that the current rasio has a positive and significant effect, debt to equity rasio has a positive and significant, and net profit margin has a positive and significant effect on firm value. Meanwhile, inventory turnover has a positive and insignificant effect on firm value. Simultaneously current rasio, inventory turnover, debt to equity rasio and net profit margin have a significant effect on firm value.